A interculturalidade no ensino de línguas estrangeiras: problematizando o termo competência comunicativa intercultural - Paiva, Aline Fraiha (2015)
The term interculturality is increasingly in evidence in the studies focusing mainly on the educational, political, economic and social contexts. Therefore, also in the field of foreign language teaching and learning, there are many works based on intercultural issues (Byram, 2000; Fantini, 2000; Mendes, 2004). However, it is possible to identify different approaches, and one of them which often stands out in discussions of the area is related to intercultural (communicative) competence. In this work we aim to develop a reflection on the relationship between the terms communicative competence and interculturality, in order to understand the potential uses of the term intercultural (communicative) competence and its implications, and to identify possible referrals for understanding the term interculturality in context of language teaching and learning. This Applied Linguistics research is characterized as a bibliographical, interdisciplinary and qualitative-interpretative based study. Through this research, we could understand more deeply ideas as competence, intercultural (communicative) competence and interculturality, and we have critically approached the relationship that has been established between these terms in the field of foreign language teaching and learning, especially in the context of Portuguese as a foreign/ second language. We believe that the discussions that bring out the notion of interculturality are symptoms of a society that aims to build a common horizon, so that the otherness can have its free space of expression assured. We understand, therefore, that intercultural issues should not be restricted to the level of skills/ competences in the practice of foreign language teaching. Interculturality could be understood as an invitation to reflection and action committed to the difference and the (co)experiences that take place inside and outside the classroom; a kind of driving force able to assist and guide teachers in their pedagogical planning, in the approach adopted by them to develop the communicative competence of their students, as well as in their attempt to raise students' and the other agents' awareness in the learning process for a careful and respectful attitude towards the “other”.